EFFECT OF WORK MOTIVATION, WORK RULES AND WORKLOAD ON THE PERFORMANCE OF LECTURERS IN UNIVERSITIES - Bambang Moertono Setiawan; Zulhawati Zulhawati; Joko Sutopo (AIBPM Publisher, 2019)
The challenge of lecturers in improving competency and competition is one of the references in the development of higher education institutions. Lecturers become one of the elements of success in achieving the vision and mission of universities or colleges. So that in order to achieve the target or goal, it is supported by achieving good lecturer performance. In this study, we will discuss how the relationship of improving the quality of performance and motivation of all levels in achieving a superior university through. University performance can be influenced by work motivation, workload and work rules. In order to achieve the most effective performance, special attention is needed for the performance of lecturers as the primary implementers of the education process in higher education. The purpose of this study was to analyse the positive direct effect of work motivation, workload and work rules on the performance of lecturers in universities. The object of this study took data at the University of X. Where in this study the analysis carried out on the performance of the lecturer with this variable showed the direct work motivation results on the performance of the lecturer. Other variables can also be seen from the organisation's work and workload in the organisation, if appropriately needed, it will produce good competence and quality of service from the three things needed by associations, research and community service in higher education.